Early Neurological Deterioration Despite Recanalization in Basilar Artery Occlusion Treated by Endovascular Therapy - Zhong, Xi; Tong, Xu; Sun, Xuan; Gao, Feng; Mo, Dapeng; Wang, Yilong; Miao, Zhongrong (Frontiers in Neurology, 2020)
Objective: We aim to identify the risk factors of early neurological deterioration (END) despite successful recanalization and explore the association of END with 90-day outcomes in acute basilar artery occlusion (BAO) treated by endovascular therapy (EVT). Methods: A prospectively registered consecutive cohort of BAO patients with successful recanalization by EVT in a tertiary stroke center during a six-year period was reviewed. END was defined as an NIHSS score increase ≥ 4 points, or death, from baseline to 24 hours after EVT. Multivariate logistic regression analysis was used to identify the risk factors of END. The 90-day outcomes between END and non-END groups were compared by Pearson’s Chi-squared test. Results: END was observed in 21 of 148 patients included in this study. Multivariate logistic regression analysis showed that patients with progressive or fluctuating symptoms had a higher risk of END than those with symptoms of acute attack (OR = 5.235.52, 95% CI = 1.63-17.261.73-17.63), and NIHSS score and puncture-to-recanalization time (PTR), as continuous variables, were also significantly associated with END. Using a generalized additive model with spline smoothing function, we observed a linear relationship between PTR (increased by 1 hour) and END (OR = 2.422.57, 95% CI = 1.34-4.31.45-4.57), and a nonlinear relationship between NIHSS score and END. Only when the NIHSS score was ≥ 23 points was it related to END (OR = 0.7, 95% CI = 0.6-0.9). Additionally, patients with END had a lower proportion of 90-day favorable outcome (19.0% vs. 59.1%, P < 0.01) and higher mortality (33.3% vs. 13.4%, P = 0.048) than those with Non-END. Conclusion: Mode of stroke onset, NIHSS score, and PTR may help to identify BAO patients with a higher risk of END after EVT. Moreover, END may affect the 90-day outcomes of these patients. Keywords Basilar artery; Acute stroke; Revascularization; Prognostic factor; Endovascular treatment